Phase I trial with a combination of docetaxel and (153)Sm-lexidronam in patients with castration-resistant metastatic prostate cancer - Lin, Jianqing (2009)
BACKGROUND: This study was designed to evaluate toxicity and preliminary efficacy of 2 cycles of concomitant standard dose/schedule of (153)Sm-lexidronam plus Q 3 weeks schedule escalating doses of docetaxel in metastatic castration-resistant prostate cancer (mCRPC). METHODS: mCRPC patients with progressive bone metastases were treated in 4 cohorts. Docetaxel doses were escalated from 50, 50, 0 mg/m(2) (on days 1, 22, 43, per 12-week cycle) to 75, 75, 75 mg/m(2). (153)Sm-lexidronam was administered on days 2 (Q 12 weeks) at dose of 1 mCi/kg/cycle (maximum of 2 cycles). RESULTS: Thirteen patients received an average of 3.6 doses of docetaxel (range, 2–6 doses, median 4) and 1.5 doses of (153)Sm-lexidronam (range, 1–2, median 2). Toxicity was primarily hematologic. There were total 35 episodes grade 3/4 neutropenia with a median 7 (range 7–14) days to recovery to ≤grade 1. One dose limiting grade 3 thrombocytopenia occurred on cohorts 3 and 4. Eight of 13 (62%) patients had PSA > 50% decrease as best response during the treatment. Median time to bone disease progression was 5.2 months (range 91 days–10 months+); 6/13 (46%) patients had stable/improved bone scans at 6 months and 6/6 (100%) symptomatic patients had improvement in pain. CONCLUSIONS: Concurrent 6-month administration of 4 doses (75 mg/m(2)) of standard Q 3 weeks schedule of docetaxel with 2 Q 3 months infusions of 1 mCi/Kg (153)Sm-lexidronam is feasible with reversible bone marrow suppression, and deserves further testing in mCRPC patients with extensive bone metastasis.